Aroclor 1254 and BDE-47 inhibit dopaminergic function manifesting as changes in locomotion behaviors in zebrafish embryos. (February 2018) - Tanaka, Yasuaki; Fujiwara, Mari; Shindo, Asako; Yin, Guojun; Kitazawa, Takio; Teraoka, Hiroki
Abstract: Contamination with polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) in the environment is a major concern due to their persistent bioaccumulative toxicity that can disturb neurobehavioral functions including movements. Recently, it was reported that some PBDE including BDE-47 stimulates locomotor activities of zebrafish embryos by unknown mechanism. In this study, motor movements of the zebrafish embryo were used as a model system to evaluate the neuronal toxicity of a non-coplanar PCB-dominant mixture (Aroclor 1254) and BDE-47. Both organohalogens increased tail shaking and rotation of embryos in a concentration-dependent manner. Chemical inhibition and gene knock-down of tyrosine hydroxylase and vesicular monoamine transporter 2 (VMAT2) also induced hyperactivities. Hyperactivities induced by these treatments were all inhibited by supplementation of l -tyrosine and l -dopa, precursors of dopamine synthesis. Both organohalogens reduced dopamine contents and increased the 3, 4-dihydroxyphenylacetic acid (DOPAC)/dopamine ratio in whole embryos. The results suggest that functional inhibition of dopaminergic neurons is involved in hyperactivities of zebrafish embryos caused by Aroclor 1254 and BDE-47. Highlights: Aroclor 1254 and BDE-47 caused hyperactivities in zebrafish embryos. Inhibition of tyrosine hydroxylase and VMAT2 also induced hyperactivities. Hyperactivities by these treatments were inhibited by precursors of dopamine synthesis. Organohalogens reduced dopamine contents and increased the DOPAC/dopamine ratio.